2012
DOI: 10.1177/0022034512460402
|View full text |Cite
|
Sign up to set email alerts
|

The Antimicrobial Peptide, LL-37, Inhibitsin vitroOsteoclastogenesis

Abstract: Uncoupled bone resorption leads to net alveolar bone loss in periodontitis. The deficiency of LL-37, the only human antimicrobial peptide in the cathelicidin family, in patients with aggressive periodontitis suggests that LL-37 may play a pivotal role in the inhibition of alveolar bone destruction in periodontitis. We aimed to investigate a novel function of LL-37 in osteoimmunity by blocking osteoclastogenesis in vitro. Human osteoclast progenitor cells were isolated from a buffy coat of blood samples. The ce… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
36
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 29 publications
0
36
0
2
Order By: Relevance
“…More recently, evidence has accumulated that the antiinfective effects of HDPs are also the result of their immunomodulatory properties such as upregulation of expression of chemokines that, in turn, recruit and activate host immune cells [6,14,15,19,28,38]. HDPs can also modulate production of pro-and antiinflammatory cytokines to control the inflammatory response [14,15,19,28,38] and can inhibit osteoclast differentiation [20,40] and thereby potentially can reduce inflammatory osteolysis and the lethal consequences of septic shock. As a result of their unique immunomodulatory mechanisms of action, HDPs are also less likely to induce bacterial resistance than are conventional antibiotics [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…More recently, evidence has accumulated that the antiinfective effects of HDPs are also the result of their immunomodulatory properties such as upregulation of expression of chemokines that, in turn, recruit and activate host immune cells [6,14,15,19,28,38]. HDPs can also modulate production of pro-and antiinflammatory cytokines to control the inflammatory response [14,15,19,28,38] and can inhibit osteoclast differentiation [20,40] and thereby potentially can reduce inflammatory osteolysis and the lethal consequences of septic shock. As a result of their unique immunomodulatory mechanisms of action, HDPs are also less likely to induce bacterial resistance than are conventional antibiotics [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…CRAMP and LL-37 share 47% identity and 67% similarity in their amino acid sequences. Therefore, these observations raised the question of whether LL-37 and CRAMP have similar activities or have distinct activities, which might account for the different results obtained by us and by Supanchart et al 32 A candidate target for different actions of CRAMP/LL-37 was the P2X 7 purinergic receptor. LL-37 enhanced ATP-induced Ca 2+ influx mediated by the human P2X 7 receptor, 33 while CRAMP inhibited it mediated by the mouse P2X 7 receptor.…”
Section: Discussionmentioning
confidence: 74%
“…32 reported that LL-37 suppressed RANKL-induced osteoclastogenesis in human peripheral blood mononuclear cell (PBMC) cultures. CRAMP and LL-37 share 47% identity and 67% similarity in their amino acid sequences.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the earlier studies were not entirely convincing, the idea was proposed that CRAMP and the human analog LL-37 could serve as an osteoblast-derived protector in bacterial infection-induced osteoclastic bone reabsorption [3,4]. In this issue of J Mol Med, Park and colleagues pursue this idea further by investigating humanβ-defensin-3 C-15 (HBD3) and any role that small peptide could have in inhibiting bone reabsorption by impairing osteoclast activity [5].…”
mentioning
confidence: 99%